Hubungan Penerapan Good Corporate Governance (GCG) dengan Risiko Financial Perbankan - Maretha Rissi, Dita; Amelia Herman, Lisa (Akuntansi dan Manajemen, 2020)
This research is a quantitative study. The purpose of this study was to determine the relationship between the implementation of good corporate governance (GCG) and the financial risk of banking at Bank Nagari, starting from 2015-2019. In the principles of good corporate governance (GCG), there are principles of transparancy, accountability, responsibility, independence and fairness. This research is built on the belief that by implementing GCG in Bank Nagari, the Bank has a strong internal management and can automatically minimize financial risks that can harm Bank Nagari. The data collection methods used in this study were interviews and documentary studies conducted at the Compliance Work Unit and the Risk Management Division at Bank Nagari, Padang Head Office. The data obtained were analyzed using the Spearman Rank Correlation method. The results of this study indicate that there is a very strong relationship between the implementation of good corporate governance (GCG) and banking financial risk at Bank Nagari, where the implementation of good GCG principles is believed to strengthen the internal conditions of Bank Nagari effectively and efficiently as well as financial risk. minimized. In addition, the research results also show that the motivation of Bank Nagari in implementing GCG from 2015-2019 is getting better based on the results of self-assessments that are conducted annually.